Bromidotetrakis(2-isopropyl-1H-imidazole-κN3)copper(II) bromide - Anna Dołęga; Katarzyna Baranowska; Joanna Socha; Sylwia Godlewska (Acta Crystallographica Section E, 2011)
The CuII atom in the title salt, [CuBr(C6H10N2)4]Br, is coordinated in a square-pyramidal geometry by four imidazole N atoms and one bromide anion that is located at the apex of the pyramid. The cations and the anions form a two-dimensional network parallel to (001) through N—H...Br hydrogen bonds.